PEDAGOGICAL DOCUMENTATION IN EARLY CHILDHOOD EDUCATION IN THE LIGHT OF STUDIES PRODUCED IN THE AREA - Medeiros, Rodolfo de Oliveira [UNESP]; Medeiros, Amanda de Araújo Passamai; de Castro, Rosane Michelli [UNESP]; Higa, Elza de Fátima Ribeiro; Mascarin, Aline Maria Noli; Donadai, Kelly Cristina Encide de Vasconcelos; Tédde, Cláudia [UNESP] (Ludomedia Unipessoal Lda, 2023)
Introduction: Early childhood education has been recognized as a fundamental aspect for the overall development of the child, with the school being the space where conditions are provided for intentionally planned pedagogical offers, offering conditions for children to exercise the role of social actor and subject of rights. On this premise, pedagogical documentation, a strategy contemplated in current participatory pedagogies, has emerged as a relevant tool in the Early Childhood Education scenario, requiring practical appropriation to obtain successful results. Objective: To understand this centrality of pedagogical documentation as a contemplated strategy for implementing participatory pedagogies in Early Childhood Education, according to the literature on the subject. Method: Literature review, carried out in the Scientific Electronic Library Online (Scielo), Educational Resources Information Center (ERIC), Scopus and Google Scholar databases, in the period between October 2022 and November 2022. Results: Three analytical bases, namely: An investigative practice, pedagogical documentation and observation and records in pedagogical documentation. Final considerations: It was evidenced that, in practice, the pedagogical documentation impacts on conditions for children's reflection on their experiences, impelling them to be inserted in investigative activities based on their problematizations, during the pedagogical process in Early Childhood Education and, as a two-way street, it offers conditions for the self-training of male and female teachers, with an emphasis on reflection on teaching practices.
DOCUMENTAÇÃO PEDAGÓGICA NA EDUCAÇÃO INFANTIL À LUZ DOS ESTUDOS PRODUZIDOS NA ÁREA
Keywords: Child education; Literature review; Participatory Pedagogies; Pedagogical Documentation